2010
DOI: 10.1096/fj.09-152207
|View full text |Cite
|
Sign up to set email alerts
|

miRNA 34a, 100, and 137 modulate differentiation of mouse embryonic stem cells

Abstract: MicroRNAs (miRNAs) play an important role in proper function and differentiation of mouse embryonic stem cells (ESCs). We performed a systematic comparison of miRNA expression in undifferentiated vs. differentiating ESCs. We report that 138 miRNAs are increased on the induction of differentiation. We compared the entire list of candidate mRNA targets of up-regulated miRNAs with that of mRNA down-regulated in ESCs on induction of differentiation. Among the candidate targets emerging from this analysis, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 44 publications
2
119
1
1
Order By: Relevance
“…MicroRNAs-200 are in fact known to suppress the expression of BMI1, SOX2, KLF4 9 and SIRT1, 10 whereas miR-34a to target SIRT1. 11 Moreover, our bioinformatics research by TargetScan (http:// www.targetscan.org/) indicated the other stem cell markers we analyzed SCA1, FOXA1 and SIRT1 as putative targets of miR-200 family, and KLF4 as a target of miR-34a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs-200 are in fact known to suppress the expression of BMI1, SOX2, KLF4 9 and SIRT1, 10 whereas miR-34a to target SIRT1. 11 Moreover, our bioinformatics research by TargetScan (http:// www.targetscan.org/) indicated the other stem cell markers we analyzed SCA1, FOXA1 and SIRT1 as putative targets of miR-200 family, and KLF4 as a target of miR-34a.…”
Section: Resultsmentioning
confidence: 99%
“…9,20,21 MiR-34a, first identified as direct transcriptional target of p53, 22 has been found to regulate apoptosis, 23,24 expression of metabolic enzymes in the liver 16 and embryonic stem cells differentiation. 11 We gathered a number of evidences regarding Snail: (1) hepatic stem cells constitutively express Snail; (2) their spontaneous differentiation into hepatocytes is underlined by negative regulation of Snail expression; (3) Snail silencing causes downregulation of stemness markers; (4) its ectopic expression in hepatocytes is sufficient both to restore expression of several stemness markers and (5) to repress miR-200c and -34a. This latter activity is probably due to a direct mechanism as suggested by the binding of endogenous Snail to miR-200c and -34a promoters in RLSC and in RLSCdH induced to EMT by TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…As miR-34a, which is a direct target of p53, has been well-characterized as an apoptosis executor through direct targeting of apoptosis-related genes including bcl-2, it is very likely that the distinctive regulation of miR-34a accounts for the differential apoptosis mechanism observed between MSCs and De-MSCs on oxidative stress. Conversely, a role for miR-34a in cell differentiation has been recently reported [63][64][65]. Intriguingly, Aranha et al has demonstrated that overexpression of miR-34a increases the proportion of postmitotic neurons in distinct models of neural differentiation including mouse embryonic stem cells and neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…17 We have studied the expression profiles of miRNAs during mouse ESC differentiation. 18 Among these miRs, we found that miR-125a regulates the fine balance between BMP4 and Nodal/Activin pathways in the initial phases of ESC differentiation. 19 This regulation occurs through an efficient auto-regulatory loop in which BMP4 controls the transcription of miR-125a that targets the BMP4 co-receptor, Dies1.…”
mentioning
confidence: 86%